Idiopathic Regression in Down Syndrome - Ayomipo Amiola; Manilka Brahmana; Ignatius Gunaratna; Regi Alexander (BJPsych Open)
Aims: Idiopathic Regression in Down Syndrome (IRDS) is reported to be present in 16% of people with Down syndrome however the clinical presentation is heterogeneous with no universal diagnostic criteria. It often presents in adolescence or early adulthood and there are often no known triggers. Common symptoms include language regression, mood symptoms, psychotic phenomena, motor symptoms and loss of previously acquired cognitive skills.